Optimization of the Preparation Process of Glucuronomannan Oligosaccharides and Their Effects on the Gut Microbiota in MPTP-Induced PD Model Mice - Baoxiang Wang; Lihua Geng; Jing Wang; Yuxi Wei; Changhui Yan; Ning Wu; Yang Yue; Quanbin Zhang (Marine Drugs, 2024)
Parkinson’s disease (PD) is a prevalent neurodegenerative disorder, and accumulating evidence suggests a link between dysbiosis of the gut microbiota and the onset and progression of PD. In our previous investigations, we discovered that intraperitoneal administration of glucuronomannan oligosaccharides (GMn) derived from Saccharina japonica exhibited neuroprotective effects in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mouse model. However, the complicated preparation process, difficulties in isolation, and remarkably low yield have constrained further exploration of GMn. In this study, we optimized the degradation conditions in the preparation process of GMn through orthogonal experiments. Subsequently, an MPTP-induced PD model was established, followed by oral administration of GMn. Through a stepwise optimization, we successfully increased the yield of GMn, separated from crude fucoidan, from 1~2/10,000 to 4~8/1000 and indicated the effects on the amelioration of MPTP-induced motor deficits, preservation of dopamine neurons, and elevation in striatal neurotransmitter levels. Importantly, GMn mitigated gut microbiota dysbiosis induced by MPTP in mice. In particular, GM2 significantly reduced the levels of Akkermansia, Verrucomicrobiota, and Lactobacillus, while promoting the abundance of Roseburia and Prevotella compared to the model group. These findings suggest that GM2 can potentially suppress PD by modulating the gut microbiota, providing a foundation for the development of a novel and effective anti-PD marine drug.